2006
DOI: 10.1128/iai.01560-05
|View full text |Cite
|
Sign up to set email alerts
|

Babesia microti Primarily Invades Mature Erythrocytes in Mice

Abstract: Babesia microti is a tick-borne red blood cell parasite that causes babesiosis in people. Its most common vertebrate reservoir is the white-footed mouse. To determine whether B. microti invades reticulocytes, as does the canine pathogen B. gibsoni, we infected the susceptible inbred mouse strains C.B-17.scid and DBA/2 with a clinical isolate of B. microti. Staining of fixed permeabilized red blood cells with 4,6-diamidino-2-phenylindole or YOYO-1, a sensitive nucleic acid stain, revealed parasite nuclei as lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…In contrast, erythrocyte death results in replacement of the mature parasite-permissive erythrocytes with less mature reticulocytes and this repopulation correlates with the appearance of intra-erythrocyte crisis forms and parasite clearance. This is consistent with a previous study that showed that B. microti primarily invades mature erythrocytes in mice and reticulocytes are rarely infected (43). That study concluded that the intensity of reticulocytosis varied with the degree of parasitemia, and that the timing of reticulocytosis appeared to be delayed in susceptible (DBA/2 C.B.10.scid) versus resistant strains of mice (C.B-17, BALB/cBy, B10.D2.).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, erythrocyte death results in replacement of the mature parasite-permissive erythrocytes with less mature reticulocytes and this repopulation correlates with the appearance of intra-erythrocyte crisis forms and parasite clearance. This is consistent with a previous study that showed that B. microti primarily invades mature erythrocytes in mice and reticulocytes are rarely infected (43). That study concluded that the intensity of reticulocytosis varied with the degree of parasitemia, and that the timing of reticulocytosis appeared to be delayed in susceptible (DBA/2 C.B.10.scid) versus resistant strains of mice (C.B-17, BALB/cBy, B10.D2.).…”
Section: Discussionsupporting
confidence: 93%
“…On days 7, 14, 28, and 42 after nymphal infestation of P. leucopus mice, 50 µL of peripheral blood were obtained via submandibular venipuncture. Blood cells were fixed in glutaraldehyde, permeabilized in Triton X-100, and treated with DNase-free RNase, as previously described [50] . Parasites were detected using the nucleic acid dye YOYO-1 iodide.…”
Section: Methodsmentioning
confidence: 99%
“…NYLS3, an IgG1 monoclonal antibody (MAb) that recognizes PyExp1 (PyHep17) was a kind gift from Stefan Kappe (Seattle Biomedical Research Institute, Seattle, WA) (34). Rat anti-mouse CD71 (BD Biosciences, San Jose, CA) and mouse anti-human CD71 (eBiosciences, San Diego, CA) were used to stain mouse and human reticulocytes, respectively (35,36). Preparations of host cell cytoplasmic and parasite-associated proteins were evaluated by immunoblotting using polyclonal rabbit anti-P. falciparum aldolase (Abcam, Cambridge, MA) and rabbit antiPyMSP8 (37).…”
Section: Methodsmentioning
confidence: 99%